0791 Effects of Low Frequency Electrical Stimulators as Nonpharmacological Treatment in Restless Legs Syndrome. (27th May 2020) - Cho, Y; Lee, Y; Ku, J; Kim, K
Abstract: Introduction: Non-pharmacological treatments for restless legs syndrome (RLS) is a treatment option for patients who have not yet started medical treatment, who do not respond to their prescribed medication, or who suffer from adverse effects of medication. This study aims to investigate the clinical effectiveness of low frequency electronic stimulators (LFES) as a non-pharmacological treatment. Methods: This is a randomized, single-blind study. After screening 64 patients according to the inclusion/exclusion criteria, a total of 46 patients participated in the study. The participants were separated into an active group and a sham group with 22 and 24 members, respectively. The stimulation was administered using the tapping mode (3Hz) present on the machines used, and symptom changes were measured in both groups. The effects of the stimuli were analyzed with repeated measures ANOVA. Results: Symptom severity was significantly reduced in the active group, and showed significant interaction effects in the time multiple group. Although both the active and sham groups reported improved symptoms upon receiving longer periods of treatment, the effect of the LFES was greater in the active group. Conclusion: Analyzing the effects of LFES by dividing the active and sham groups revealed that LFES treatment resulted in symptom improvement when using effective stimulation intensity. LFES can be a non-pharmacological treatment option for RLS. Support: None